2021
DOI: 10.12688/f1000research.52159.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental-analytical approach to assessing mechanosensitive cartilage blood marker kinetics in healthy adults: dose-response relationship and interrelationship of nine candidate markers

Abstract: Purpose: To determine the suitability of selected blood biomarkers of articular cartilage as mechanosensitive markers and to investigate the dose-response relationship between ambulatory load magnitude and marker kinetics in response to load.  Methods: Serum samples were collected from 24 healthy volunteers before and at three time points after a 30-minute walking stress test performed on three test days. In each experimental session, one of three ambulatory loads was applied: 100% body weight (BW); 80%BW; 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…MMP-3 has also been shown to be mechanosensitive; either a single injurious compression or cyclic supra-physiologic compression results in upregulation of MMP-3 and subsequent proteoglycan loss and cartilage degradation. [25][26][27][28] Mechanical injury with forces similar to what would be borne by the cartilage at the time of articular fracture has been shown to upregulate MMP-3 between 10-fold and 250-fold. 29,30 As such, future work is needed to better understand the mechanobiologic response to injury and the role of mechanobiologic mechanisms on PTOA progression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3 has also been shown to be mechanosensitive; either a single injurious compression or cyclic supra-physiologic compression results in upregulation of MMP-3 and subsequent proteoglycan loss and cartilage degradation. [25][26][27][28] Mechanical injury with forces similar to what would be borne by the cartilage at the time of articular fracture has been shown to upregulate MMP-3 between 10-fold and 250-fold. 29,30 As such, future work is needed to better understand the mechanobiologic response to injury and the role of mechanobiologic mechanisms on PTOA progression.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS-4 was log transformed to address skewness. Because we intended to only interpret results that are in concordance with previous evidence for mechanosensitivity, 45 we refrained from applying Bonferroni corrections and set the significance level to 0.05. Statistical analysis was performed in R version 4.0.3 (The R Foundation, Vienna, Austria).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggested that COMP, MMP-3, MMP-9, ADAMTS-4, CPII and IL-6 could suitable for assessing in vivo cartilage mechanosensitivity. 45 It is possible that these markers may reflect individual disease progression despite of the lack of group results. Joint load assessed during gait analysis can be considered a surrogate of the typical loading of an individual's joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations